Restorative narrative as contextual journalistic reporting. (June 2019) - Dahmen, Nicole Smith
Restorative narrative, a recently termed contextual news form, reports on the responses of communities and individuals in the wake of traumatic events or systemic dysfunction. Through textual analysis of restorative narrative reporting and in-depth interviews with the corresponding journalists, this research seeks to understand how restorative narrative fits into the landscape of modern journalistic reporting.